Do Chinese viewers watch e-sports games for a different reason? Motivations, attitude, and team identification in predicting e-sports online spectatorship - Shi, Minlong; Ren, Ruqin (Frontiers in Psychology, 2023)
Introduction Understanding factors that predict the intention of e-sports game online spectatorship has drawn a great deal of scholarly attention. Prior work on this topic has primarily focused on explaining the mediation mechanism between the spectator motivations and behavioral intention, such as attitude and subjective well-being, while overlooking the specific role of team identification and satisfaction with past experience, which were understudied in the previous studies but also prominent in the context of e-sports spectatorship. Besides, previous research was mainly conducted in a Western context; therefore, little was known about the online e-sports audience in China and their motivations to view e-sports games on live-streaming platforms. Methods The current study thus aims to examine if and how these factors are related to the intention of watching e-sports games online by hierarchical regression and structural equation modeling. Results Results from a survey of 452 Chinese e-sports online audiences suggested that three motivations (skill improvement, entertainment, and friends bonding), attitude towards e-sports game online spectatorship, and satisfaction with past experience were positively related to watching intention. These motivations and satisfaction also positively influenced attitude, while socialization opportunity (one of the motivations) negatively influenced attitude. Furthermore, team identification negatively moderated the relationship between satisfaction with past experience and behavioral intention. Also, attitude mediated the association between motivations, satisfaction, and behavioral intention. Discussion In general, our study identifies the motivations that relate to Chinese e-sports viewers’ attitude as well as their watching intention, and underscores the role of satisfaction with past experience, attitude, and team identification in the context of e-sports. These findings contribute to deriving a holistic view of e-sports game online spectatorship.